Finite element modeling of material removal rate in micro-EDM process with and without ultrasonic vibration. Issue 3 (26th March 2020) - Choubey, Mayank; Maity, K.P.; Sharma, Abhishek
Abstract : Purpose: This research explores the finite element modeling of the crater and material removal rate (MRR) in micro-electrical discharge machining (micro-EDM) with and without vibration of the workpiece. The application of workpiece vibration in the micro-EDM process improved flushing efficiency and enhanced material removal rate (MRR). Design/methodology/approach: In this work, the two-dimensional axisymmetric finite element method (FEM) has been developed to predict the shape of the crater with and without vibration. The temperature distribution on the workpiece surface with and without vibration has been obtained in the form of the contour plot. Findings: The MRR obtained from the numerical model revealed that there was an enhancement in MRR in micro-EDM with vibration as compared to without vibration. The effect of process parameters on MRR in micro-EDM with and without is also presented in this work. Originality/value: In this work, the two-dimensional axisymmetric FEM model has been developed to predict the shape of the crater with and without vibration.